SAT0383 Using MRI synovitis to count involved joints in the ACR/EULAR 2010 RA criteria increases their sensitivity and specificity. (23rd January 2014) - Duer-Jensen, A.; Hørslev-Petersen, K.; Bak, L.; Johansen, J.S.; Hansen, M.S.; Hetland, M.L.; Ejbjerg, B.J.; Lindegaard, H.M.; Vinterberg, H.; Møller, J.; Østergaard, M.
Abstract : Objectives: In a prospective cohort study of patients with undifferentiated arthritis (UA) to investigate the ability of ACR/EULAR 2010 criteria with or without different MRI variables to diagnose RA, considering ACR 1987 criteria as gold standard reference Methods: 119 pts (≥2 tender/swollen joints in MCP, PIP, wrist or MTP joints for >6 wks but <24 mths) without a rheumatological diagnosis, underwent clinical (68SJC/68TJC), biochemical, X-ray and MRI (unilateral wrist, MCP, PIP and MTP, scored by OMERACT RAMRIS (MTP not scored for synovitis (syn))) examinations and were followed for >12 mths. Sensitivity, specificity, accuracy, positive/negative predictive value (PPV/NPV) for diagnosing RA by 1) using ACR/EULAR 2010 criteria with and without including MRI syn, 2) substituting 68SJC/68TJC with MRI syn or 3) incorporating MRI bone oedema (BE) in the criteria are shown in Table. Results: ACR/EULAR criteria with MRI syn variables included, gave a slight increase in sensitivity (Table, row 2-4) compared to without MRI (row 1). BE increased the sensitivity even more, highest with BE in wrist and/or MTP joint (row 5-8). Highest sensitivity, specificity, agreement and PPV were demonstrated when 68SJC/68TJC was replaced with counting only joints with MRI syn (row 9-11). Using syn ≥1 as cut-off (row 9) the sens, spec, accuracy, PPV and NPV were all higher than using the criteria based on clinical examination (row 1). Conclusions: When fulfilment of the ACR 1987 criteria at follow-up is considered the gold standard reference, substituting IJC with MRI synovitis in joints of one hand, markedly increases the sensitivity and specificity of the ACR/EULAR 2010 criteria in UA. Disclosure of Interest: None Declared